2016
DOI: 10.1117/12.2239261
|View full text |Cite
|
Sign up to set email alerts
|

Understanding charge transfer processes on metal oxides: a laser-flash-photolysis study

Abstract: In the focus of this study, mixtures of commercially available TiO2 powders were created and their photocatalytic activity concerning the acetaldehyde degradation in the gas phase was tested. Further, the lifetime of the photogenerated charge carriers was analyzed by Laser-Flash-Photolysis-Spectroscopy. The acetaldehyde degradation experiments of the mixed powders lead to positive and negative deviations from the expected weighted mean. Nevertheless, their photocatalytic activity could be correlated with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…72 Interestingly, Sieland et al found that longer charge carrier lifetimes in TiO 2 actually correlated with lower photocatalytic conversion of acetaldehyde, although the actual reason was not clear. 73 Patrocinio reported that their TiO 2 sample exhibiting faster recombination had higher efficiencies for photocatalytic oxidation, attributed to its larger surface area that offsets poorer electronic properties. 74 However, interestingly, the sample surface area had little effect on H 2 evolution, and the efficiency of electron transfer (ET) from TiO 2 to platinum co-catalysts was the primary factor affecting photocatalytic performance for H 2 evolution.…”
Section: Charge Carrier Dynamics Measured By Tasmentioning
confidence: 99%
“…72 Interestingly, Sieland et al found that longer charge carrier lifetimes in TiO 2 actually correlated with lower photocatalytic conversion of acetaldehyde, although the actual reason was not clear. 73 Patrocinio reported that their TiO 2 sample exhibiting faster recombination had higher efficiencies for photocatalytic oxidation, attributed to its larger surface area that offsets poorer electronic properties. 74 However, interestingly, the sample surface area had little effect on H 2 evolution, and the efficiency of electron transfer (ET) from TiO 2 to platinum co-catalysts was the primary factor affecting photocatalytic performance for H 2 evolution.…”
Section: Charge Carrier Dynamics Measured By Tasmentioning
confidence: 99%